The Urgency of Notarial Deeds in the Transfer of Plant Variety Protection Rights - Afif, M. Nalina Zaky; Sesung, Rusdianto (PT. Hafasy Dwi Nawasena, 2025)
This research discusses the urgency of notarial deeds in the transfer of plant variety protection rights, focusing on the regulations governing the aforementioned matters and the applicable laws and regulations. This normative legal research utilizes primary legal sources, including Law No. 29 of 2000 on Plant Varieties, Law No. 02 of 2014 on Amendments to Law No. 30 of 2004 on Notary Positions, and Presidential Regulation of the Republic of Indonesia No. 14 of 2004 on the Requirements and Procedures for the Transfer of Plant Variety Protection and the Use of Protected Varieties by the Government. The article concludes by examining the legal force of notarial deeds in the transfer of plant variety protection rights and the laws regulating these matters.